1998
DOI: 10.1097/00000658-199801000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Radical Systematic Mediastinal Lymphadenectomy in Patients With Resectable Non-Small Cell Lung Cancer

Abstract: Radical systematic mediastinal lymphadenectomy does not influence disease-free or overall survival in patients with NSCLC and without overt lymph node involvement. However, a small subgroup of patients with limited mediastinal lymph node metastases might benefit from a systematic lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0
11

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(166 citation statements)
references
References 15 publications
2
153
0
11
Order By: Relevance
“…[15] reported in a prospective study that for NSCLC of stage I, systematic lymph node dissection could remove the tumor cells more thoroughly and reduce the postoperative risk of recurrence and distant metastasis. Izbicki, et al [16] reported that systemic lymph node dissection did not improve the survival rate in patients of state N0. In a retrospective study, Ishiguro, et al [17] reported that, there was no statistical significance in the 5-year survival rate between the way of intraoperative lobe-specific lymph node dissection and systematic lymph node dissection in patients with stage I NSLCL.…”
Section: Discussionmentioning
confidence: 99%
“…[15] reported in a prospective study that for NSCLC of stage I, systematic lymph node dissection could remove the tumor cells more thoroughly and reduce the postoperative risk of recurrence and distant metastasis. Izbicki, et al [16] reported that systemic lymph node dissection did not improve the survival rate in patients of state N0. In a retrospective study, Ishiguro, et al [17] reported that, there was no statistical significance in the 5-year survival rate between the way of intraoperative lobe-specific lymph node dissection and systematic lymph node dissection in patients with stage I NSLCL.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been a limited number of randomized prospective trials that had compared SND with LS in patients with NSCLC (4,5,19). Izbicki (4) and Wu (5) investigated patients with a wide range of clinical stages which included clinical stage I to IIIA, while Sugi (19) investigated a rather limited population which included patients with peripheral lung cancer smaller than 2 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…With the examination of the stage migration, survival according to the pathological stage, which may be affected by spurious downstaging caused by inadequate staging, should be reviewed. Izbicki (4) described that insufficiency in staging accuracy of LS might have affected poorer outcome of small group of patients with limited lymph node involvement (pN1 disease or single-level pN2 disease). In our study, there was no significant difference in pN0 cases between the SND group and the LS group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] There are still many questions left unanswered regarding selection of surgical candidates and whether adjuvant CT and/ or RT should be provided before or after surgery, as well as the optimal drugs, dose, order, and number of adjuvant treatment modalities. 13 After surgical resection, Okada et al found that 48.9% of patients with T3N0 disease and 21.1% of patients with N2 disease survived 5 years.…”
Section: Resectable Diseasementioning
confidence: 99%